Kopi di Dunia Islam: Antara Sunnah, Kesehatan, dan Tradisi Sosial - Fikri Alamsyah; Muhammad Wildy Luthfi Hasan Muliyadi; Lucky Fernando (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
Coffee is a drink that has deep meaning in the Islamic world, covering spiritual, health and social aspects. This study method uses a literature approach by collecting and analyzing the latest research regarding the role of coffee in the context of the sunnah, health benefits and social traditions among Muslims. The study results show that coffee is not only considered a halal drink and beneficial for health, but also as a symbol of brotherhood and strong cultural identity, strengthening social relations in various Muslim communities around the world.